Investigating GDF5-Induced tenogenesis in mesenchymal stem cells for the potential improvement of tendon repair / Tan Sik Loo - Tan, Sik Loo (2013)
Mesenchymal stem cell (MSC) has an immense potential for use in clinical applications, however, there is still paucity in the fundamental knowledge in the techniques and processes involved in MSCs differentiation, especially tenogenic differentiation. Growth and differentiation factor 5 (GDF5) is a potential inducer which may induce tenogenic differentiation response in MSC. The aims of this current study were: (1) to investigate the tenogenic differentiation in human and rabbit MSCs (hMSCs and rbMSCs respectively) in response to GDF5 treatment; (2) to investigate the potential of GDF5-induced rbMSCs in tendon repair in in vivo rabbit model; and (3) to investigate the differentially expressed genes between GDF5-induced hMSCs and the untreated hMSCs compared to the native tenocytes (hTeno). In this study, both hMSCs and rbMSCs were isolated and characterized following the ISCT guidelines. Upon GDF5 (0, 5, 25, 50, 100 and 500 ng/ml) treatment, the results demonstrated that there was (i) no significant differences in the proliferation rate between the hMSCs cultured at different concentrations of GDF5; (ii) a significant increase in total collagen levels comparable to that of hTeno culture (p<0.05) when hMSCs were cultured at 100 ng/mL of GDF5, (iii) a significant increase in total collagen levels in 500 ng/ml GDF5-induced rbMSCs to a level comparable to rbTeno (rabbit tenocyte) cultures, however there were no significant difference in total collagen levels between rbMSCs treated with 100 ng/ml and 500 ng/ml of GDF5; (iv) a significant (p<0.05) up-regulation in the expression of candidate tenogenic marker genes (Scleraxis (Scx), tenascin-C and type-I collagen (Col-I)) whilst a significant (p<0.05) down-regulation of the non-tenogenic marker genes (runt-related transcription factor 2 and sex determining region Y (SRY)- box 9) at day 7 upon 100 ng/mL GDF5 treatment in hMSCs; (v) a significant increase in Scx and Col-I gene expression levels were also detected in 100 ng/ml GDF5-induced rbMSC; (vi) increase in COL-I expression at protein level in rbMSCs cultures treated with 100 ng/ml GDF5. In the in vivo study to investigate the potential use of tenogenic rbMSCs (TMSC, 100 ng/mL of GDF5-induced rbMSCs), the quality of the infraspinatus tendon repair in New Zealand white rabbits using TMSCs and other methods were evaluated, which showed significant improvement in the cell based treated groups compared to the non-cell-based treated groups. A significant upregulation in expression of tenogenic marker genes (Scx and Col-I) in TMSCs group as compared to other treatment groups were also observed. Furthermore, microarray analysis showed: (i) significant differences in 954 genes in GDF5-induced hMSC and tenocytes compared to control hMSCs; (ii) the differentially expressed genes were involved in specific pathways (i.e. cytoskeleton remodeling, cell adhesion, and extracellular matrix related genes) that are closely related to the native behavior of hTeno in vivo. The findings of this study demonstrate that concentration of GDF5, ≥100 ng/mL is able to induce tenogenic differentiation in both hMSCs and rbMSCs. These data suggest that tenogenic MSCs may potentially provide similar function to that of native tenocytes e.g. during tendon repair. These findings provide evidence of potential use of GDF5-induced MSCs in the clinical applications in future.